Organizational culture on of small and medium performance: the role of entrepreneurial orientation as mediator - Albarry Ilmi; Perengki Susanto (Universitas Negeri Padang, 2021)
This study aims to examine the influence of organizational culture on the performance of small and medium enterprises (SMEs) mediated by entrepreneurial orientation. All leaders or owners of SMEs in the commodity of superior business products/services in Pariaman City are the population in this study. The sampling technique used a non-probability approach, namely the purposeful sampling technique. The number of samples used in the data analysis was 218 samples, but only 202 samples met the requirements. This study uses a variance-based structural equation modeling (VB-SEM) approach using Smart-PLS software. The findings of this study indicate that (i) organizational culture has a positive and significant effect on the performance of SMEs, (ii) organizational culture has a positive and significant effect on entrepreneurial orientation, (iii) entrepreneurial orientation has a positive and significant effect on the performance of SMEs, (iv) organizational culture has a significant effect on positive and significant impact on the performance of SMEs through entrepreneurial orientation. The managerial implications of this research are discussed later.